Efficacy of virtual reality balance training on rehabilitation outcomes following anterior cruciate ligament reconstruction: A systematic review and meta-analysis - Chao Du; Nei-Meng Gu; Tian-Ci Guo; Ai-Feng Liu (PLoS ONE, 2025)
Objective The objective of this systematic review and meta-analysis is to clarify the rehabilitation efficacy of virtual reality (VR) balance training after anterior cruciate ligament reconstruction (ACLR). Methods This meta-analysis was registered in PROSPERO with the registration number CRD42024520383. The electronic databases PubMed, Web of Science, Cochrane Library, MEDLINE, Embase, China National Knowledge Infrastructure, Chinese Biomedical Literature, China Science and Technology Journal Database, and Wanfang Digital Periodical database were systematically searched to identify eligible studies from their inception up to January 2024. The investigated outcomes included International Knee Documentation Committee (IKDC) score, visual analogue scale (VAS), Holden grading, Extensor peak torque (EPT), Flexor peak torque (FPT), knee reaction time, knee reproduction angle difference. The pooled mean difference (MD) and 95% confidence intervals (CIs) were calculated using the random-effects model. Results Six RCTs with a total of 464 patients after unilateral ACLR were included for 8–12 weeks of VR balance training intervention. Analysis of the results showed that compared with the conventional rehabilitation control group, the VR balance training group significantly improved the International Knee Documentation Committee (IKDC) score (MD = 3.88, 95%CI: 0.95~6.81), Holden grading (MD = 0.42, 95%CI: 0.33~0.51), Extensor peak torque (EPT) (MD = 12.03, 95%CI: 3.28~20.78)and Flexor peak torque (FPT) (MD = 14.57, 95%CI: 9.52~19.63) in postoperative ACLR patients, and significantly reduced knee reaction time (MD = -0.30, 95%CI: -0.35~-0.25), knee angle reproduction difference at 30° (MD = -0.88, 95%CI: -1.16~-0.61), knee angle reproduction difference at 60° (MD = -0.80, 95%CI: -1.09~-0.50), and VAS score (MD = -0.52, 95%CI: -0.65~-0.39). Conclusion Since many of the included results are based on low—or very—low—quality evidence, although the results show a certain trend, the conclusion has great uncertainty. In the rehabilitation training following ACLR and lower—limb balance training, the application of VR might be advantageous for the recovery of patients’ knee joint function, lower—limb muscle strength, proprioception, and pain management. The level of immersion may influence the rehabilitation outcome. Because of the limitations in data quality and heterogeneity as well as the small sample size, the strength of the conclusions is weakened. These findings should be verified in further large-scale prospective studies.